Moonlighting functions of the NRZ (mammalian Dsl1) complex - Tagaya, Mitsuo; Arasaki, Kohei; Inoue, Hiroki; Kimura, Hana (Frontiers in Cell and Developmental Biology, 2014)
The yeast Dsl1 complex, which comprises Dsl1, Tip20, and Sec39/Dsl3, has been shown to participate, as a vesicle-tethering complex, in retrograde trafficking from the Golgi apparatus to the endoplasmic reticulum. Its metazoan counterpart NRZ complex, which comprises NAG, RINT1, and ZW10, is also involved in Golgi-to-ER retrograde transport, but each component of the complex has diverse cellular functions including endosome-to-Golgi transport, cytokinesis, cell cycle checkpoint, autophagy, and mRNA decay. In this review, we summarize the current knowledge of the metazoan NRZ complex and discuss the “moonlighting” functions and intercorrelation of their subunits.